Ceilometer CL51 raw data measured during POLARSTERN cruise PS125, links to files - Holger Schmithüsen (PANGAEA, 2021)
The meteorological observatory Polarstern continuously operates a ceilometer to measure cloud height and vertical visibility. The instrument features an upward pointing pulsed diode laser centered at a wavelength of 910nm. Using Light Detection and Ranging (LIDAR) technology the instrument records the backscatter, predominantly caused by hydrometeors such as precipitation and cloud particles. Measurements are taken approximately every 36 seconds. All data published here is left "as recorded", no quality control was applied.